2015
DOI: 10.1002/advs.201500118
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Materials Interface for Efficient Capture of Circulating Tumor Cells

Abstract: Originating from primary tumors and penetrating into blood circulation, circulating tumor cells (CTCs) play a vital role in understanding the biology of metastasis and have great potential for early cancer diagnosis, prognosis and personalized therapy. By exploiting the specific biophysical and biochemical properties of CTCs, various material interfaces have been developed for the capture and detection of CTCs from blood. However, due to the extremely low number of CTCs in peripheral blood, there exists a need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 127 publications
(164 reference statements)
0
49
0
Order By: Relevance
“…14,15,58 An individual fluorescently stained CTC with a strong fluorescence signal could be clearly identified under the microscope (Figure 5d). …”
Section: Isolation Individual Release and Genetic Analysis Of Ctcs Fmentioning
confidence: 98%
“…14,15,58 An individual fluorescently stained CTC with a strong fluorescence signal could be clearly identified under the microscope (Figure 5d). …”
Section: Isolation Individual Release and Genetic Analysis Of Ctcs Fmentioning
confidence: 98%
“…It also offers a distinct advantage over molecular techniques since the downstream processing can include both genotypic and phenotypic analysis of intact single cells as well as cell culture, drug testing, and other assays1213. Although CTCs are rare cells (typically ~1–100 per mL) and therefore challenging to detect, microfluidics has emerged as an important tool for CTC isolation that potentially enables detection, diagnosis, prognosis, drug screening, and understanding of cancer biology121314151617. A very recent study showed that automated slide-based immunofluorescence has potential to detect MM cells with a sensitivity of better than 1 in 10 6 nucleated cells in blood (below 10 cells/mL blood)18, but it requires sample preparation and staining of slides and a high-throughput fluorescence scanner.…”
mentioning
confidence: 99%
“…Nanomaterials, due to high surface‐area‐to‐volume ratio, compatible capture, and release capabilities, have drawn much attentions in CTCs' isolation since they can improve sensitivity and specificity for capture efficiency . Until now, carbon nanotubes, silicone, gold, and graphene oxide nanoparticles have been extensively utilized in the affinity‐based capture methods . It has been demonstrated that porous microposts fabricated by carbon nanotubes can reduce hydrodynamic obstruction and ameliorate fluid flow near the surface leading to enhanced targeted CTCs and antibody interactions .…”
Section: D Microfluidic Platforms For Ctcs' Detection and Isolationmentioning
confidence: 99%